Estimation of soil and grout thermal properties for energy piles: A new parameter estimation method. Issue 7 (October 2021) - Zeng, S; Yan, Z; Yang, J
Abstract: It is critical to determine the thermal parameters of the soil and pile for designing energy piles. Based on the infinite different-thermal properties cylindrical heat source model, this paper proposes a method that can use short-term thermal response test (TRT) data to estimate the soil thermal conductivity, thermal diffusivity and thermal resistance in the pile. A three-dimensional numerical model was established and verified by a large sandbox test. The numerical model was used to generate virtual TRT data, and the pattern search algorithm was adopted to estimate the parameters. Then the accuracy of the parameter identification results was discussed. It is found that, compared with the previous methods, the proposed method can greatly shorten the time required for TRT. At the same time, this method can estimate the thermal parameters more accurately, especially the soil thermal conductivity that has the greatest impact on heat transfer performance, with an estimated error of 1.23%.